The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11064-008-9738-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Mouse Hypothalamus under Simulated Microgravity

Abstract: Exposure to altered microgravity during space travel induces changes in the brain and these are reflected in many of the physical behavior seen in the astronauts. The vulnerability of the brain to microgravity stress has been reviewed and reported. Identifying microgravity-induced changes in the brain proteome may aid in understanding the impact of the microgravity environment on brain function. In our previous study we have reported changes in specific proteins under simulated microgravity in the hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…Data are expressed as mean ± SEM (n = 8). * P \ 0.05, ** P \ 0.01 compared with the static control group Neurochem Res (2010) 35:1445-1454 1451 shows that the nervous system is especially vulnerable to oxidative stress during microgravity conditions [5][6][7][8]. With continuing advancements in aerospace technology and more prolonged space flights, two things will become increasingly important in order to ensure the safety of prolonged space travel: an increased understanding-at both the organismal and cellular levels-of the effects of microgravity on the nervous system, and the taking of some effective measurements to achieve this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are expressed as mean ± SEM (n = 8). * P \ 0.05, ** P \ 0.01 compared with the static control group Neurochem Res (2010) 35:1445-1454 1451 shows that the nervous system is especially vulnerable to oxidative stress during microgravity conditions [5][6][7][8]. With continuing advancements in aerospace technology and more prolonged space flights, two things will become increasingly important in order to ensure the safety of prolonged space travel: an increased understanding-at both the organismal and cellular levels-of the effects of microgravity on the nervous system, and the taking of some effective measurements to achieve this.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation products (malondialdehyde, MDA) are increased in rats that are tail-suspended for 2 or 3 weeks to simulate microgravity [5,6]. A previous study detected lowered glutathione, decreased superoxide dismutase 2 (SOD2), and increased malate dehydrogenase and peroxiredoxin-6 in the hypothalamus of mice exposed to SMG, reflecting a reduction of antioxidant system function [7]. In another study, ROS are increased-with a concomitant decrease in glutathione-in brain stem and frontal cortex of mice exposed for 7 days to SMG [8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a proteomic analysis of hippocampus of HU mice revealed changes in structural proteins coupled with the loss of proteins involved in cell metabolism (Sarkar et al 2006). Furthermore, a similar analysis performed in hypothalamus revealed alteration of biomarkers of oxidative stress indicating vulnerability of the hypothalamus to the stress generated by microgravity (Sarkar et al 2008). …”
Section: Introductionmentioning
confidence: 91%
“…Previous cDNA microarray experiments showed that ten genes in human T lymphocytes were upregulated and 79 downregulated under simulated microgravity (Lewis et al 2001). Besides, GST and superoxide dismutase-2 decreased in the mouse hypothalamus under simulated microgravity through two-dimensional gel and matrix-assisted laser desorption ionization time of flight analysis (Sarkar et al 2008).The results obtained here indicate that microgravity cannot always elevate the amount of the recombinant protein expression under any circumstance, which was at least related with the target protein and temperature. However, the underlying mechanism still needs to be further investigated in the future study.…”
Section: Discussionmentioning
confidence: 54%